1995
DOI: 10.1093/gerona/50a.1.m28
|View full text |Cite
|
Sign up to set email alerts
|

The Activities-specific Balance Confidence (ABC) Scale

Abstract: The present study provided additional psychometric support for the FES. However, the greater item responsiveness of the ABC scale makes it more suitable to detect loss of balancing confidence in more highly functioning seniors. Greater situation-specificity of items may also assist clinicians in targeting appropriate interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

20
1,661
8
33

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,337 publications
(1,722 citation statements)
references
References 14 publications
20
1,661
8
33
Order By: Relevance
“…Prior to testing, all amputees completed the activities-specific balance confidence (ABC) scale [10][11][12], a self-efficacy measure assessing balance confidence across 16 specific activities on an analogue scale (0-100%).…”
Section: Methodsmentioning
confidence: 99%
“…Prior to testing, all amputees completed the activities-specific balance confidence (ABC) scale [10][11][12], a self-efficacy measure assessing balance confidence across 16 specific activities on an analogue scale (0-100%).…”
Section: Methodsmentioning
confidence: 99%
“…Amputees filled in two questionnaires to determine their activity level and balance confidence, respectively, the modified amputee activity score (AAS) [17,18] and the activities-specific balance confidence scale (ABC) [19][20][21]. AB only filled out the latter questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…7 Although fall-related physical morbidities are significant, arguments have been made that the psychological consequences associated with falling, such as developing a fear of falling and/or losing balance confidence, are of equal or greater concern due to their subsequent influence on reduced quality of life and self-imposed avoidance of activities. 8,9 Among the psychological consequence of falling, Miller et al 10 found balance confidence, the belief individuals have in their ability to perform daily activities without losing their balance, 11 to have a greater influence on mobility and participation in daily and social activities than fear of falling among individuals with a lower-limb amputation. Balance confidence as such is important to assess among those in this population.…”
mentioning
confidence: 99%
“…At present there are three balance confidence measures, including, the Activities-specific Balance Confidence (ABC) scale, 11 the Confidence in maintaining Balance Scale (CONFbal), 17 and the Balance Self-perceptions Test. 18 The ABC-scale, however, is by far the most widely used measure to assess balance confidence.…”
mentioning
confidence: 99%
See 1 more Smart Citation